HUBUNGAN FUNGSIONAL ANTARUNSUR DALAM FRASE BAHASA INDONESIA - Efri Yades; Leni Syafyahya (JURNAL ARBITRER, 2016)
This article aims to explain the phrase Indonesian. In this case will be described functional relationship between elements in the phrase and  meaning that occur as a result of relationship. To achieve the objectives of this study, collected from spoken and written language. On the data is collected, analyzed by a unified and distributional. After data analysis has been done, in the presence of a functional relationship bet ween elements found in the phrase. Functional relationships between elements in the phrase endocentric is the core and modifiers, while the phrase exocentric is the relator and the axis. Meaning generated as a result of functional  relationship between elements in endocentric phrases such as: property, amount, type, state, and processes. However, the meaning of which is generated in the phrase exocentric among others: the direction, places, destination, origin, and sustainability.